Mutation in the RNA-Dependent RNA Polymerase of a Symbiotic Virus Is Associated With the Adaptability of the Viral Host - Lu, Hong; Li, Jing; Yang, Pengcheng; Jiang, Fei; Liu, Hongran; Cui, Feng (Frontiers in Microbiology, 2022)
Host adaptation has the potential to cause rapid genetic variation in symbiotic microorganisms in insects. How mutations in symbiotic viruses favor viral fitness in hosts and even influence host adaptability to new environments remains elusive. Here, we explored the role of genetic divergence at one site of a symbiotic virus, acyrthosiphon pisum virus (APV), in the host aphid’s adaptation to unfavorable plants. Based on the transcriptomes of the pea aphid Vicia faba colony and Vicia villosa colony, 46 single nucleotide polymorphism (SNP) sites were found in the APV genomes from the two aphid colonies. One SNP at site 5990, G5990A, located at the RNA-dependent RNA polymerase (RdRp) domain, demonstrated a predominance from G to A when the host aphids were shifted from V. faba to the low-fitness plants V. villosa or Medicago sativa. This SNP resulted in a substitution from serine (S) to asparagine (N) at site 196 in RdRp. Although S196N was predicted to be located at a random coil far away from conserved functional motifs, the polymerase activity of the N196 type of RdRp was increased by 44.5% compared to that of the S196 type. The promoted enzymatic activity of RdRp was associated with a higher replication level of APV, which was beneficial for aphids as APV suppressed plant’s resistance reactions toward aphids. The findings showed a novel case in which mutations selected in a symbiotic virus may confer a favor on the host as the host adapts to new environmental conditions.